Pembentukan Karakter Siswa Melalui Pembiasaan Budaya Religius di MTs Al Mujahidin - Janatul Saidah; Moh. Syamsul Falah (Jurnal Pendidikan Madrasah, 2023)
This study discusses the implementation of religious culture in shaping the character of students at MTs Al Mujahidin Cikarang Utara, Bekasi. This study aims to explore in-depth information about how to shape student character through habituation of religious culture in schools. This research uses a qualitative approach with a type of case study research with data collection methods in the form of observation, interviews and documentation. The results showed that the formation of student character was carried out by socialization, habituation, and punishment methods. These three methods are carried out so that students can follow the applicable rules and form the character of students who are disciplined and responsible.